Trust as a mediation of transformational leadership relationships and welfare of hotel employees psychology - Yustisia Kristiana; Rosdiana Sijabat; Niko Sudibjo; Innocentius Bernarto (Jurnal Pariwisata Pesona, 2022)
The hotel industry is one that is vulnerable to crises such as the COVID-19 pandemic. The condition can create an uncertain outlook for the hotel industry due to a decline in demand. This condition can create vulnerability for employees. Transformational leadership influences employees' psychological well-being and trust that the most significant thing about the link between transformational leaders and their employees. The objective of this study is to examine the effect of (1) transformational leadership on trust; (2) transformational leadership on psychological well-being; (3) trust on psychological well-being; and (4) trust as a mediator in the correlation between transformational leadership and psychological well-being. This study is a quantitative study, with a cross-sectional approach. The sampling technique was purposive sampling with 162 employees from 4 and 5-star hotels in DKI Jakarta Province as respondents. Data analysis using PLS-SEM. The findings revealed that the four hypotheses proposed in the study, and the results of data analysis showed that all the hypotheses stated were accepted. The implication of this research is to become a reference for management to improve psychological well-being by developing transformational leadership and trust. This study has limitations, in future research, it would be possible to examine the overall employee well-being and be carried out in other locations to overcome the limitations of the study.